Prisoner of cabin 13 - Vornholt, John. (New York : Pocket Books, 1998)
Sabrina is excited about being a counselor at Camp Bearclaw until she is assigned to cabin 13, the troublemaker's cabin.
"An Archway paperback.".
"Based on the hit TV series.".
6.5
3-6
Keywords: Camp counselors -- Fiction; Witches -- Fiction; Witches -- Fiction